Classification of the nickel-like silver spectrum (AgXX) from a fast capillary discharge plasma - Rocca, Jorge J., author; Rahman, A., author; Wyart, J.-F., author; Physica Scripta, publisher (Colorado State University. Libraries, 2004)
A study of the Ni-like silver (AgXX) spectra in the 13:7-20:5 nm wavelength region using a plasma generated by a fast high power capillary discharge is reported. Forty-three AgXX transitions have been identified with the assistance of calculations performed using the Slater-Condon method with generalized least-squares fits of the energy parameters. The average difference between the measured transition wavelengths and the theoretical values is 0.0026 nm.